The Influence Of Leadership And Reward Style On Employee Performance (Case Study: DPRD Offices Seluma District) - Eska Prima Monique Damarsiwi; Nurzam Nurzam; Suswati Nasution (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Human resources are an important factor in globalization to face competition among organizations. Leadership style can be defined as an individual ability to be able to organize, direct, motivate employees to be able to help run an organization. The quality of a leader can be recognized if he can influence, direct and improve employee performance in carrying out all assigned tasks. Rewards will usually be given to employees who have contributed to advancing the company in accordance with the standards set by management. The sample used in this research is 34 employees who have become Civil Servants at the DPRD Office of Seluma Regency. Data collection using a questionnaire and the method of analysis used is multiple regression. Before the regression test was carried out, the validity and readability test would be carried out on the data used in the study. From the hypothesis testing, it is found that the leadership style variable (X1) and the reward variable (X2) have a partially significant relationship to employee performance (Y). The amount of the determinant coefficient is 0.590, which means that the independent variables X1 and X2 will be able to influence the dependent variable Y by 59% while the remaining 41% is influenced by other variables outside of this study. While simultaneously the variables X1 and X2 have a simultaneous effect on variable Y